Structure and Function of Bacteriophage R17 Replicative Intermediate Ribonucleic Acid II. Properties of the Parental Labeled Molecule - Erikson, R. L. (1967)
Replicative intermediate ribonucleic acid (RNA), designated RI, which contained parental RNA labeled with (32)P was separated by filtration through agarose from the nucleic acids prepared from (32)P-labeled RNA phage-infected Escherichia coli. A larger amount of ribonuclease-sensitive parental label was found in the rapidly sedimenting forms of RI than in the slower sedimenting forms, indicating that parental RNA is displaced to form a single-stranded tail. This result indicates that some phage RNA is generated by asymmetric semiconservative replication of RI, but it does not mean that a portion of the RI duplexes cannot be conserved during generation of phage RNA. Parental RNA was also found in double-stranded RNA with no apparent tails which sedimented with an S value of 13. This RNA was soluble in 2 m NaCl, and its sedimentation rate was unaffected by ribonuclease; nevertheless, single-strand scissions were produced by ribonuclease and were detected after the duplex was converted to its component single strands.